2007
DOI: 10.1088/0957-4484/18/48/485706
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing superplasticity of engineering ceramics by introducing BN nanotubes

Abstract: Introducing carbon nanotubes (CNTs) into polymer or ceramic matrices has been a promising approach to obtain ultra-strong, extra-toughened materials as well as multifunctional composites. Most of the previous work on CNT composites has focused on strengthening and toughening of matrix materials at ambient conditions. However, so far there is a lack of information on the mechanical behavior of these composites at elevated temperature. Recently, single-walled CNTs were found to undergo a superplastic deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 31 publications
(28 reference statements)
2
68
0
Order By: Relevance
“…Due to shorter time of sintering, SPS retains the nanostructure and improves the mechanical property of the sintered body [19,[50][51][52][53][54]. In addition, minimal dwell at high temperature causes lesser dissociation of HA into TCP [56][57][58][59][60][61].SPS of HA-CNT has employed temperatures in the range of 900 -1250 °C [42,46] , pressure of 7.5-120 MPa [42,46] in vacuum [41] or argon [31]. The systematic studies on the determination of ideal SPS temperature for HA-CNT system found 1100°C…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to shorter time of sintering, SPS retains the nanostructure and improves the mechanical property of the sintered body [19,[50][51][52][53][54]. In addition, minimal dwell at high temperature causes lesser dissociation of HA into TCP [56][57][58][59][60][61].SPS of HA-CNT has employed temperatures in the range of 900 -1250 °C [42,46] , pressure of 7.5-120 MPa [42,46] in vacuum [41] or argon [31]. The systematic studies on the determination of ideal SPS temperature for HA-CNT system found 1100°C…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…Poor wear resistance of HA is one of the shortcomings for its application as orthopedic implant [28,38,59,61,84]. …”
Section: Tribological Properties Of Ha-cnt Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors argued that the content and distribution of CNTs in ceramics impact the grain boundary sliding during deformation. Huang et al 52) showed that the presence of boron nitride BN nanotubes in alumina enhanced the superplastic behavior of the composite through the mechanism of inhibition of both static (in the assintered composite) and dynamic grain growth (after compressive deformation) in the ceramic matrix.…”
Section: Promising Properties Of Composites Achieved By the Network Dmentioning
confidence: 99%
“…Recently, Huang et al reported that addition of small amount of BN nanotubes (BNNTs) (0.5 wt%) into alumina and silicon nitride ceramics made them more ductile at moderate temperatures than corresponding pristine ceramics [7]. The static grain growth in the as-sintered BNNT/alumina and the following dynamic grain growth after compressive deformation are dramatically inhibited.…”
Section: Introductionmentioning
confidence: 99%